The effect of CFTR modulators on structural lung disease in cystic fibrosis - Mok, L. Clara; Garcia-Uceda, Antonio; Cooper, Matthew N.; Kemner-Van De Corput, Mariette; De Bruijne, Marleen; Feyaerts, Nathalie; Rosenow, Tim; De Boeck, Kris; Stick, Stephen; Tiddens, Harm A. W. M. (Frontiers in Pharmacology, 2023)
Background: Newly developed quantitative chest computed tomography (CT) outcomes designed specifically to assess structural abnormalities related to cystic fibrosis (CF) lung disease are now available. CFTR modulators potentially can reduce some structural lung abnormalities. We aimed to investigate the effect of CFTR modulators on structural lung disease progression using different quantitative CT analysis methods specific for people with CF (PwCF). Methods: PwCF with a gating mutation (Ivacaftor) or two Phe508del alleles (lumacaftor-ivacaftor) provided clinical data and underwent chest CT scans. Chest CTs were performed before and after initiation of CFTR modulator treatment. Structural lung abnormalities on CT were assessed using the Perth Rotterdam Annotated Grid Morphometric Analysis for CF (PRAGMA-CF), airway-artery dimensions (AA), and CF-CT methods. Lung disease progression (0 to 3 years) in exposed and matched unexposed subjects was compared using analysis of covariance. To investigate the effect of treatment in early lung disease, subgroup analyses were performed on data of children and adolescents aged <18 years. Results: We included 16 modulator exposed PwCF and 25 unexposed PwCF. Median (range) age at the baseline visit was 12.55 (4.25 to 36.49) years and 8.34 (3.47 to 38.29) years, respectively. The change in PRAGMA-CF %Airway disease [-2.88 (-4.46, -1.30), p=0.001] and %Bronchiectasis extent [-2.07 (-3.13, -1.02), p<0.001] improved in exposed PwCF compared to unexposed. Subgroup analysis of paediatric data showed that only PRAGMA-CF %Bronchiectasis [-0.88 (-1.70, -0.07), p=0.035] improved in exposed PwCF compared to unexposed. Conclusion: In this preliminary real-life retrospective study CFTR modulators improve several quantitative CT outcomes. A follow-up study with a large cohort and standardization of CT scanning is needed to confirm our findings.